Irritable bowel syndrome and biliary tract pathology. Clinical analysis - T. E. Polunina (Медицинский совет, 2020)
Irritable bowel syndrome (IBS) – a recurrent functional disorder of the gastrointestinal tract (GIT), the main symptom of which is abdominal pain necessarily associated with a change in intestinal function. IBS is a functional intestinal disorder in which recurrent abdominal pain is associated with a defecation act and a change in the frequency or shape of the stool. The diagnosis of IBS remains exclusively clinical. The difficulty in studying IBS, especially from the perspective of its epidemiology, is that there is still no universal and specific biological marker. Very often patients complain about symptoms typical for several functional disorders, in particular, biliary tract pathology and IBS. The article discusses the multi-component causes and mechanisms of IBS formation, which are also present in other functional gastrointestinal tract diseases. Patients with IBS often have functional disorders of the biliary tract (FDBT) that are not associated with organic pathology. There are no reliable differences in the frequency and nature of FDBT in patients with IBS, depending on its current variant - with constipation or diarrhea prevalence. As a result, the treatment of patients with IBS remains a challenge, and the recurrence of the disease depends on the state of psycho-emotional health, the presence of overlap syndrome in most cases. The article presents the main international criteria for diagnostics of IBS. The main approaches to the treatment of IBS are considered. Good results in the treatment of IBS are observed when using drugs that affect the complex of pathophysiological mechanisms of the disease. This is confirmed in the article by a clinical case study. The prescription of the Sparex drug for pain relief in a patient with IBS and FDBT is justified by the fact that it not only eliminates pain, but also improves the rheological properties of bile, typical for overlap “IBS-FDBT” syndrome.